Diogenes syndrome - causes and treatment of pathological hoarding and self neglect - Czarnota-Kuczyńska, Julia; Cichoń, Katarzyna; Chyćko, Małgorzata; Trąbka, Natalia; Demidowicz, Gabriela; Younes, Martyna; Lasota, Nina; Wiśniewski, Wojciech; Lambach, Maciej; Kowalczyk, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction Diogenes syndrome is a behavioral disorder typically described in physically neglected people living in extreme poverty, unsanitary conditions and self-imposed isolation, who often refuse outside help and tend to accumulate unusual objects. This syndrome is gaining increasing attention in the world of neurology and psychiatry. The aim of the study To summarize current knowledge on the causes of Diogenes syndrome, its characteristics and treatment. Material and methods The search of the Pubmed and Google Scholar database was carried out using keywords, in order to find the latest publications. Summary Diogenes syndrome is a complex disease that will affect an increasing number of elderly people as the population ages. There is a lack of extensive research to create clear diagnostic criteria, classification and treatment for Diogenes syndrome. The creation of a disease entity would enable earlier diagnosis and help patients.